Characterization of organic solar cell materials by G‐SIMS. (31st July 2012) - Franquet, A.; Conard, T.; Voroshazi, E.; Poleunis, C.; Cheyns, D.; Vandervorst, W.
<x xml:space="preserve">Abstract</x> In this study, the gentle SIMS (G‐SIMS) method has been applied to organic solar cell materials. Various primary ion conditions were used to generate the G‐SIMS spectra; monoatomic and cluster sources with different energies were tested. It is shown that the G‐SIMS concept helps to identify both PCBM and P3HT materials through the enhancement of molecular and characteristic ions of the two molecules. Copyright © 2012 John Wiley & Sons, Ltd.